Characterization of the pore structure of metakaolin-derived geopolymers by neutron scattering and electron microscopy - Maitland, Clinton; Buckley, Craig; O'Connor, Brian; Butler, P.; Hart, Robert (BLACKWELL PUBLISHING, 2011)
The pore-solid structure of selected high-compressive-strength metakaolin geopolymers has been characterized to facilitate quantitative prediction of their physical properties. Geopolymers are multiphase materials with pore widths ranging from subnanometre to several tenths of a millimetre. Ultramicrotoming of resin-embedded grains was found to be an effective method for producing electron-transparent sections. Scanning and transmission electron microscopy showed the existence of a bi-level pore system and heterogeneity of the pore morphology. Ultra-small-angle neutron scattering, of sufficiently thin specimens, was found to be useful in detecting the length scales on which statistically significant structural changes occur as the geopolymer chemical composition is varied. Contrast variation experiments confirmed that the small-angle neutron scattering from an Si:Al:Na = 2.5:1:1.2 geopolymer before and after dehydration was dominated by scattering from pores. These experiments suggested the presence of closed (under current experimental conditions) pores in the dehydrated geopolymer. A three-phase analysis was developed for this system, and the scattering of the solid, open pore and closed pore phases was determined as a function of scattering length density ρ. The scattering from all three phases had the same q dependence over the range of likely ρ within the uncertainties.A lower limit of 4.21 (6) × 1010 cm-2 was determined for the scattering length density ρw of the nondehydrated geopolymer by assuming the pore fluid to be water. This scattering length density is significantly higher than the expected value of approximately 3.4 × 1010 cm-2. Small-angle neutron scattering from the dehydrated and nondehydrated Si:Al:Na = 2.5:1:1.2 geopolymer showed that dehydration does not cause a severe change in morphology of the nanoporosity on the length scale probed.